A new species of Candolleomyces (Psathyrellaceae) from Pakistan - Ahmad, Ishtiaq; Haqnawaz, Muhammad; Niazi, Abdul Rehman; Khalid, Abdul Nasir (Phytotaxa, 2024)
A new species, Candolleomyces amygdaliformis, is described from Pakistan, based on morpho-anatomically, and phylogenetic analysis of combined ITS and LSU sequences. Morpho-anatomically, the new taxon is characterized by a light brownish gray pileus with a reddish brown center and a decurved margin, a light gray, shiny stipe, and amygdaliform to phaseoliform basidiospores. Phylogenetically it clusters with another species C. campanulatus from Pakistan. Illustrated morphological description, phylogenetic analyses and comparisons with morphologically similar or phylogenetically related species as well as a key to the known species from Pakistan are provided.